Őri Fülep Gábor életműve - BÁTORINÉ MISÁK, Marianna (Studia Universitatis Babes-Bolyai Theologia Reformata Transylvanica, 2023)
Gábor Fülep Őri’s Oeuvre. Gábor Fülep Őri was the Bishop of the Tiszáninnen Reformed Church District between 1799 and 1823. He was born in Sajószentpéter on 25 April 1739 and died also here in 1823. He was educated in his native village, Miskolc, and Sárospatak. During his years of peregrination, he visited Franeker and Utrecht. In the latter place, he obtained a doctorate in 1765. On his return home, he was first a chaplain with his father and from 1768 an independent pastor in Aszaló. In 1773, he was elected professor at the Reformed College of Sárospatak, and for twenty-five years he educated the future pastors of the church district. During this time, he has held the post of Rector-Professor eight times, which, in addition to his teaching and creative work, involved many other responsibilities. In 1797, he was elected deputy bishop to the ailing Bishop Abraham of Paks in 1797, in place of the ailing Bishop of Szathmár, and the following year he became pastor of his native village, Sajószentpéter. In 1799, after the death of Bishop Szathmári, he became full bishop. His works and translations attest to his extraordinary activity, which won him the recognition not only of his contemporaries but also of posterity.